Impact of Digitalization on Islamic Family Law - Hud Leo Perkasa Maki (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the impact of digitalization on Islamic family law through a systematic literature review. Against the backdrop of the increasing use of digital platforms and digital currencies, the aim of the research is to understand how the principles of Islamic law adapt to these technological advances. The research method involves analysis of various relevant scientific publications in reputable international journals Scopus Q1. The results of the discussion highlight the complexity and dynamics of the evolution of Islamic family law in the digital era, including implications for financial transactions, inheritance, gender equality, and customary practices. The implication of this research is the need for an in-depth understanding of the relationship between technology and the principles of Islamic law, as well as the importance of formulating relevant legal policies to overcome challenges and take advantage of opportunities in the context of digitalization.